Neonatal Jaundice Prevalence and Risk Factors at a District al Hindiya Hospital in Karbala (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Background: Some newborns have jaundice as a result of hyperbilirubinemia; nevertheless, complications can arise in a tiny percentage of instances, leading to potentially fatal outcomes. Infections and hemolysis are among the several potential causes. Finding out how often jaundice is in infants and what causes it is the main goal of this research.Materials and Methods: A Review Among newborns hospitalized to al Hindiya Hospital in Karbala, Iraq, from October 2022 to April 2023, the prevalence of neonatal jaundice was evaluated in this study. This research presents the results of a cross-sectional study of 892 neonatal inpatients.Results In all, 498 (or 54.8%) of the infants admitted were female, while 394 (or 44.4%) were male. Jaundice was seen in 664 infants (74% of the total). The majority of cases were caused by premature birth.Conclusions:  Prematurity, illness (especially septicemia), blood type incompatibility, and breastfeeding were the most prevalent causes of newborn jaundice. Because breast milk jaundice is a major contributor to chronic jaundice.